2009
DOI: 10.1073/pnas.0901074106
|View full text |Cite
|
Sign up to set email alerts
|

Structural waters define a functional channel mediating activation of the GPCR, rhodopsin

Abstract: Structural water molecules may act as prosthetic groups indispensable for proper protein function. In the case of allosteric activation of G protein-coupled receptors (GPCRs), water likely imparts structural plasticity required for agonist-induced signal transmission. Inspection of structures of GPCR superfamily members reveals the presence of conserved embedded water molecules likely important to GPCR function. Coupling radiolytic hydroxyl radical labeling with rapid H 2O 18 solvent mixing, we observed no exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
193
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 185 publications
(205 citation statements)
references
References 53 publications
11
193
0
Order By: Relevance
“…4A), participating in an extended network of ∼100 H-bonds (2,17). This network is thought to stabilize rhodopsin (2,18,19) and suppress thermal isomerization, conferring rhodopsin with extraordinary thermal stability to lower the dark noise and enhance photosensitivity. This hypothesis is supported by the observation that the rates of thermal reactions are slowed down threefold in deuterated water, consistent with a rate-determining step involving water interactions (20).…”
Section: Resultsmentioning
confidence: 99%
“…4A), participating in an extended network of ∼100 H-bonds (2,17). This network is thought to stabilize rhodopsin (2,18,19) and suppress thermal isomerization, conferring rhodopsin with extraordinary thermal stability to lower the dark noise and enhance photosensitivity. This hypothesis is supported by the observation that the rates of thermal reactions are slowed down threefold in deuterated water, consistent with a rate-determining step involving water interactions (20).…”
Section: Resultsmentioning
confidence: 99%
“…XF-MS generates hydroxyl radicals by activating bulk as well as protein-bound water, which can react directly with proximal side-chains (13,30). In contrast to bulk water, protein-bound water (identified by X-ray crystallography) shows a longer residence time in solution and facilitates a significantly higher yield of hydroxyl radical modifications at reactive residues (23,31). XF-MS has been used to probe the positions of internal water molecules, changes in the H-bonding networks involving bound water, and the dynamic role of internal water in hydrophobic cavities inside protein cores (23,26,(31)(32)(33).…”
Section: Hdx-msmentioning
confidence: 99%
“…In contrast to bulk water, protein-bound water (identified by X-ray crystallography) shows a longer residence time in solution and facilitates a significantly higher yield of hydroxyl radical modifications at reactive residues (23,31). XF-MS has been used to probe the positions of internal water molecules, changes in the H-bonding networks involving bound water, and the dynamic role of internal water in hydrophobic cavities inside protein cores (23,26,(31)(32)(33). In addition to carotenoid translocation (9), our data demonstrate two other structural changes upon photoactivation of the OCP: unfolding and release of the N-terminal helix from the CTD surface and complete dissociation of the NTD and CTD.…”
Section: Hdx-msmentioning
confidence: 99%
“…To form the Schiff base, Lys 296 must be deprotonated, the carbonyl group must be polarized, and water must be accommodated within the chromophore-binding site (1). Hydroxyl radical footprinting revealed local conformational changes in the Rho structure following its photoactivation, presumably mediated by the dynamics of both ordered water molecules and the protein (7,8). Moreover, protein footprinting combined with rapid H 2 18 O mixing methodology and deuterium-hydrogen exchange on C 2 His residues indicated that these tightly bound internal waters do not exchange with bulk solvent in ground state Rho, Meta II, or opsin (7,8).…”
mentioning
confidence: 99%
“…Hydroxyl radical footprinting revealed local conformational changes in the Rho structure following its photoactivation, presumably mediated by the dynamics of both ordered water molecules and the protein (7,8). Moreover, protein footprinting combined with rapid H 2 18 O mixing methodology and deuterium-hydrogen exchange on C 2 His residues indicated that these tightly bound internal waters do not exchange with bulk solvent in ground state Rho, Meta II, or opsin (7,8). Thus, ordered waters function as noncovalent cofactors that actively participate in transmitting the activation signal from the retinylidene-binding pocket to the cytoplasmic face of Rho, where binding of transducin occurs.…”
mentioning
confidence: 99%